Ghana Prison Officers’ Understanding and Practices of International Human Rights Instruments and Guidelines that Protect the Rights of Prisoners - Golo, Harrison Kwame (The prison journal, 2022)
Research on prison officers’ understanding and compliance with the international human rights instruments for the protection of prisoners’ rights and guidelines for justice administration remains scanty. Drawing on data from scenario-based interviews of 24 selected prison officers in the four largest prison facilities in Ghana, this article seeks to explore how Ghana prison officers understand and practice these instruments and guidelines that protect the rights of prisoners. Applying content analysis, the findings reveals that the overwhelming majority of officer participants in this study did not have adequate intellectual and practical understanding of these relevant instruments and guidelines.